Development and psychometric evaluation of the sexual satisfaction questionnaire for postmenopausal women (PWSSQ): an exploratory mixed method study protocol - Nasim Shahrahmani; Raheleh Babazadeh; Abbas Ebadi (BMC, 2024)
Abstract Background The concept of sexual satisfaction in menopausal women is very different from that in premenopausal women, and this difference is due to aging and physical, hormonal, cultural, and psychological changes. Therefore, the first step in discovering methods for assessing sexual satisfaction in postmenopausal women is to develop a measurement instrument. This study was conducted to develop and evaluate the psychometric properties of a sexual satisfaction instrument for postmenopausal women. Methods The current study is an exploratory-sequential mixed-methods research project that will be divided into two parts: qualitative and quantitative. Aligned with the primary objective of the research, which is to elucidate the concept of sexual satisfaction in postmenopausal women, the hybrid concept analysis model developed by Schwartz and Kim will be employed. This model comprises three key phases: the theoretical phase, the fieldwork phase, and the final analytical phase. Those who met the inclusion criteria and exhibited maximum variance in terms of age, educational level, employment status, and menopausal duration were recruited. The conventional content analysis will be carried out following the steps proposed by Graneheim and Lundman. Second, in the quantitative phase, the psychometric properties of the instrument were evaluated, including the content, face and construct validity and reliability via internal consistency and stability. The psychometric properties described in the COSMIN checklist will be utilized for designing the instrument. Discussion A valid and reliable scale for evaluating the sexual satisfaction of postmenopausal women should be developed, and educational content should be designed to improve the sexual satisfaction of this group of women.